1993
DOI: 10.1086/133254
|View full text |Cite
|
Sign up to set email alerts
|

The companion of the 18-day classical Cepheid YZ Carinae

Abstract: ABSTRACT. We have obtained a deep IUE spectrum of the 18-day Cepheid YZ Carinae. Flux has been detected at the level of 1-2 X 10" 15 ergs cm -2 Â -1 s -1 from 1200 to 2000 Â, which we identify as the companion in the binary system. Since this is at least partly a result of "camera artifacts" built up during a long exposure, this is an upper limit to the flux of the companion. The contribution of camera artifacts to the spectrum is discussed. Both la) are consistent with a B8 V to A0 V star.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The combination of the spectroscopic orbital elements of Gallenne et al (2018b) (which are in agreement with those determined by Anderson et al 2016) and the PMa vectors results in a companion mass of m 2 ≈ 1.9 ± 0.3 M (Paper I) for the companion of the long-period pulsator YZ Car (P = 18.2 d). The interferometric companion search by Gallenne et al (2018b) did not reveal the faint secondary, but established an upper limit of B3V on its spectral type, in agreement with the estimate of B8V-A0V from Evans & Butler (1993) and the mass derived in Paper I, which corresponds to an A-type dwarf.…”
Section: Yz Carsupporting
confidence: 81%
“…The combination of the spectroscopic orbital elements of Gallenne et al (2018b) (which are in agreement with those determined by Anderson et al 2016) and the PMa vectors results in a companion mass of m 2 ≈ 1.9 ± 0.3 M (Paper I) for the companion of the long-period pulsator YZ Car (P = 18.2 d). The interferometric companion search by Gallenne et al (2018b) did not reveal the faint secondary, but established an upper limit of B3V on its spectral type, in agreement with the estimate of B8V-A0V from Evans & Butler (1993) and the mass derived in Paper I, which corresponds to an A-type dwarf.…”
Section: Yz Carsupporting
confidence: 81%
“…He derived the preliminary spectroscopic orbital parameters, giving A164, page 7 of 21 A&A 622, A164 (2019) an orbital period of 850 d, and suggested a spectral type between B5V and A5V for this companion. Evans & Butler (1993) later tightened the range of spectral type to B8V-A0V from ultraviolet spectra of the companion. Additional RVs were obtained by Bersier (2002), but he did not revise the orbital elements.…”
Section: Yz Carmentioning
confidence: 99%
“…YZ Car was examined by Evans & Butler (1993) with IUE and using the very weak spectrum obtained they determined that the best fit to the data indicated that the companion was similar to a main‐sequence star between B8V and A0V subtypes, giving a mass range from 2.2–2.9 M ⊙ .…”
Section: Orbital Parametersmentioning
confidence: 99%
“…Because YZ Car is one of the more luminous and larger Cepheids in the sample, and the short orbital period indicates that the stars orbit quite close together, the question of mass exchange should be addressed. Coulson (1983b) and Evans & Butler (1993) concluded that with the likely companion types and the size estimated for the Cepheid, Roche lobe overflow was unlikely.…”
Section: Orbital Parametersmentioning
confidence: 99%